High-Performance Photovoltaic Hydrogen Sensing Platform with a Light-Intensity Calibration Module - Kim, Hyeonghun; Kim, Woochul; Lee, Ryeri; Cho, Sungjun; Park, Jiyoon; Pak, Yusin; Jung, Gun Young (AMER CHEMICAL SOC, 2020)
Although battery-free gas sensors ( e.g., photovoltaic or triboelectric sensors) have recently appeared to resolve the power consumption issue of conventional chemiresistors, severe technical barriers still remain. Especially, their signals varying under ambient conditions such as light intensity restrict the utilization of these sensors. Insufficient sensing performances (low response and slow sensing rate) of previous battery-free sensors are also an obstacle for practical use. Herein, a photovoltaic hydrogen (H-2)-sensing platform having constant sensing responses regardless of light conditions is demonstrated. The platform consists of two photovoltaic units: (1) a palladium (Pd)-decorated n-IGZO/p-Si photodiode covered with a microporous zeolitic imidazolate framework-8 (ZIF-8) film and (2) a device with the same configuration, but without the Sensor 2 (w/o Pd) Pd catalyst as a reference to calibrate the base current of sensor (1). The platform after calibration yields accurate response values in real time regardless of unknown irradiance. Besides, the sensing performances (e.g., sensing response of 1.57 x 10(4)% at 1% H-2 with a response time <15 s) of our platform are comparable with those of the conventional resistive H-2 sensors, which yield unprecedented results in photovoltaic H-2 sensors.
Keywords: POWERED GAS SENSOR; METAL NANOPARTICLES; STORAGE; SENSITIVITY; STABILITY; NANOTUBES; HYBRID